DEVELOPMENT OF STREAMLIT-BASED HIGHER EDUCATION RANKING INSTRUMENT BOARDS - Chudra, Glenny; Yohannis, Alfa; Setiawan, Richard (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
The dashboard is a tool used to measure and evaluate comparisons of tertiary institutions based on six main aspects, namely teaching, research, industry income, international outlook, and citation scores. (citation score). This research aims to develop an interactive and easy-to-use college ranking dashboard using the Python language. The data obtained will be taken from a website using the scrapping method, and then the data will be combined annually. The method applied in this study uses data life cycle management with essential stages, including collection, processing, analysis, visualization, and data presentation. The results of this study are expected to be able to create a website that can be used by various parties, including prospective students, parents, and researchers who plan to conduct further research. This dashboard lets users obtain relevant information and compare multiple tertiary institutions effectively and efficiently.